Androgens, oestrogens and endometrium: a fine balance between perfection and pathology. Issue 3 (September 2020) - Gibson, Douglas A; Simitsidellis, Ioannis; Collins, Frances; Saunders, Philippa T K
Abstract : The endometrium is a complex multicellular tissue that is exquisitely sensitive to the actions of sex steroids synthesised in the ovary (endocrine system). Recent studies have highlighted a previously under-appreciated role for local (intracrine) metabolism in fine-tuning tissue function in both health and disease. In this review we have focused on the impact of oestrogens and androgens on endometrial function summarising data from studies on normal endometrial physiology and disorders including infertility, endometriosis and cancer. We consider the evidence that expression of enzymes including aromatase, sulphatase and AKR1C3 by endometrial cells plays an important role in tissue function and malfunction and discuss results from studies using drugs targeting intracrine pathways to treat endometrial disorders. We summarise studies exploring the spatial and temporal expression of oestrogen receptors (ERalpha/ESR1, ERbeta/ESR2 and GPER) and their role in mediating the impact of endogenous and synthetic ligands on cross-talk between vascular, immune, epithelial and stromal cells. There is a single androgen receptor gene and androgens play a key role in stromal-epithelial cross-talk, scar-free healing of endometrium during menstruation and regulation of cell proliferation. The development of new receptor-selective drugs (SERMs, SARMs, SARDs) has reinvigorated interest in targeting receptor subtypes in treatment of disorders including endometriosis and endometrial cancer and some show promise as novel therapies. In summary, understanding the mechanisms regulated by sex steroids provides the platform for improved personalised treatment of endometrial disorders as well as novel insights into the impact of steroids on processes such as tissue repair and regeneration.